Rekontekstualisasi Moderasi Beragama dan Transformasi Puritanisme Muhammadiyah dalam Mendukung Ketahanan Pangan dan Mobilitas Sosial - Ahmad Yusuf Prasetiawan; Made Saihu; Abdul Muid Nawawi (Matan : Journal of Islam and Muslim Society, 2026)
This article examines the role of Muhammadiyah in fostering a balanced economic order, tracing its trajectory from puritanical reasoning toward religious moderation. Muhammadiyah’s religious vision serves as a form of social capital that strengthens food security initiatives. This study is a library-based inquiry employing a philosophical–historical–critical approach. The chosen analytical framework is functionalism, which emphasizes impact and explores the interrelations between religious functions and work ethic. Within this framework, functionalism observes how Muhammadiyah’s puritanism is transformed into economic consciousness, ultimately producing concrete achievements through its charitable enterprises. The findings reveal that Muhammadiyah’s puritanism is dynamic rather than static. Its puritan impulses operate more actively in the social sphere than in the theological one. Its rejection of certain rituals and traditions reflects a refusal of inefficiency. Conversely, Muhammadiyah’s moderation strengthens ethos and action, cultivating balance between worldly and spiritual life, between the physical and the metaphysical, and between spiritual and material pursuits. For Muhammadiyah, the interpretation of Qur’anic verses is assessed through practice and the benefits they generate. This pragmatic religious orientation aligns with the character of urban Muslims and represents a geo-spiritual approach that contributes to social mobility within the community.